Hubungan Antara Konformitas Dengan Kenakalan Remaja Pada Siswa/I di SMA N 1 Sinunukan - kurniawan, Bambang; Dalimunthe, Hairul Anwar (Universitas Medan Area, 2025)
The purpose of this study was to determine the correlation between conformity and juvenile delinquency among students at SMA 1 Sinunukan. This research method uses quantitative methods. The population of this study was 467 students, and the sample in this study was students who had records of juvenile delinquency at SMA N 1 Sinunukan, with a total of 199 students. The researcher used a purposive sampling technique. The results showed that there was a positive correlation between conformity and juvenile delinquency in students at SMA N 1 Sinunukan seen from the coefficient value (Rxy) = 0.578 with p = 0.000 0.050, meaning the hypothesis that there is a positive correlation between conformity and juvenile delinquency is acceptable. Likewise, with the value of the determinant coefficient (R^2) for students/I who have a value of 0.334, this is equivalent to 33.4%, meaning that the conformity of these students/I contributes 33.4% to students at SMA 1 Sinunukan. Conformity with juvenile delinquency among students at SMA 1 Sinunukan is relatively high, due to the empirical mean value being greater than the hypothetical mean value.